Utilisation of Turmeric (Curcuma longa L.) Extract as a Natural Indicator for Borax Detection in Food Products - Dea Afnun Harahap; Browin Christmas Ginting; Nadia Pentatriana Purba; Grace Yosepha Sinaga; Farel Vandano Hiskia Sebayang; Larasati Arum Utami; Nurbaity Situmorang (MO.RI Publishing, 2026)
The widespread misuse of sodium tetraborate among informal food producers highlights the urgent need for eco-friendly, independent food screening methods. This study aimed to validate the effectiveness of turmeric rhizome (Curcuma longa L.) as an initial screening instrument for borax in high-moisture food clusters. An experimental method was applied through direct visual contact testing of reactive curcumin extract against seven types of wet domestic food samples. Colorimetric test results showed that deep orange boron cyano curcumin (rosocyanine) complex formation was detected exclusively and positively in yellow noodle samples. Six other products chicken meatballs, fish balls, pempek, white tofu, vermicelli, and crackers were confirmed negative. It is concluded that the alkaline-induced structural degradation triggered by this local natural indicator demonstrates precise reactive sensitivity, is economically viable, and is applicable as a communal preventive solution for enhancing household food safety literacy.